Optimalisasi Dana Desa dengan Pengembangan Badan Usaha Milik Desa (BUM Des) Menuju Desa Mandiri - Putri Nugrahaningsih; Falikhatun Falikhatun; Jaka Winarna (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2016)
Law of The Republic of Indonesia number 6 of 2014, including its implementation regulation, has mandated that village government to be more independent in term of managing its administration and other natural resource they have, including the financial and assets management. The method used in this research is descriptive qualitative, data collection techniques include focus group discussions, in-depth interview, observation, and documentation. The place of research in the Bulusulur village, Wonogiri, Central Java. The results showed that the implementation of village fund is executed with the establishment of Village BUM which has 5 units Enterprises, that is Keceh Swimming Pool, Campgrounds, Clean Water Facilities, Waste Bank, And Integrated Agriculture. However, in practice there are some constraints such as the difference in the paradigm of the stakeholders associated with the management of the Village Funds, lack of participation of the village community in the implementation of the job program of Village BUM, and a lack of knowledge related to the establishment of work plans and financial statements of Village BUM. The solution that is proposed includes competency enhancement training to Village BUM manager, start from strategic planning, programming, budgeting, implementation, and accompaniment of the Village BUM financial statements.